Molecular characterization of gregarines from sand flies (Diptera: Psychodidae) and description of Psychodiella n. g. (Apicomplexa: Gregarinida) - Votýpka, Jan; Lantová, Lucie; Ghosh, Kashinath; Braig, Henk; Volf, Petr (The Journal of eukaryotic microbiology, 2009)
Sand fly and mosquito gregarines have been lumped for a long time in the single genus Ascogregarina and on the basis of their morphological characters and the lack of merogony been placed into the eugregarine family Lecudinidae. Phylogenetic analyses performed in this study clearly demonstrated paraphyly of the current genus Ascogregarina and revealed disparate phylogenetic positions of gregarines parasitizing mosquitoes and gregarines retrieved from sand flies. Therefore, we reclassified the genus Ascogregarina and created a new genus Psychodiella to accommodate gregarines from sand flies. The genus Psychodiella is distinguished from all other related gregarine genera by the characteristic localization of oocysts in accessory glands of female hosts, distinctive nucleotide sequences of the small subunit rDNA, and host specificity to flies belonging to the subfamily Phlebotominae. The genus comprises three described species: the type species for the new genus--Psychodiella chagasi (Adler and Mayrink 1961) n. comb., Psychodiella mackiei (Shortt and Swaminath 1927) n. comb., and Psychodiella saraviae (Ostrovska, Warburg, and Montoya-Lerma 1990) n. comb. Its creation is additionally supported by sequencing data from other gregarine species originating from the sand fly Phlebotomus sergenti. In the evolutionary context, both genera of gregarines from mosquitoes (Ascogregarina) and sand flies (Psychodiella) have a close relationship to neogregarines; the genera represent clades distinct from the other previously sequenced gregarines.
Keywords: molekulární evoluce; druhová specificita; DNA, Ribosomal; Phylogeny; Sequence Analysis, DNA; Molecular Sequence Data; Apicomplexa; Evolution, Molecular; molekulární sekvence - údaje; Female; protozoální DNA; Host-Parasite Interactions; DNA, Protozoan; zvířata; sekvenční analýza DNA; ženské pohlaví; Male; Ribosome Subunits, Small; fylogeneze; Oocysts; Species Specificity; ribozomální DNA; oocysty; Animals; mužské pohlaví; Psychodidae; interakce hostitele a parazita; malé podjednotky ribozomu